Ekstrakurikuler Pendidikan Pra Pesantren : Strategi Transisi Efektif Menuju Kehidupan Pesantren Bagi Siswa Kelas Vi Mi Miftahul Ulum Kunjorowesi Ngoro Mojokerto - Afidatusholikha - (Amaliyatu Tadris (AMYTA), 2024)
This study aims to describe the implementation and impact of the Pre-Islamic Boarding School Education extracurricular program at MI Miftahul Ulum Kunjorowesi, Mojokerto, as a form of transitional education for sixth-grade students who will continue their education in Islamic boarding schools (pesantren). Using a qualitative approach with a case study method, this research explores the implementation process, instructional materials, and program evaluation results in terms of mental readiness (cognitive), spiritual readiness (affective), and social readiness (psychomotor). The findings indicate that the program is able to improve students’ Qur’anic literacy skills, basic understanding of Islamic sciences (Nahwu, Shorof, and Pegon), discipline in worship practices, as well as students’ independence and social responsibility. Midterm and final evaluations show increased scores across all indicators, with positive support from students’ parents. The program has also proven effective in helping students adapt better to pesantren life. These findings reinforce the importance of pre-pesantren education as an effective transitional bridge within the Islamic education system. Penelitian ini bertujuan untuk mendeskripsikan implementasi dan dampak program ekstrakurikuler Pendidikan Pra-Pesantren di MI Miftahul Ulum Kunjorowesi, Mojokerto, sebagai bentuk pendidikan transisi bagi siswa kelas VI yang akan melanjutkan pendidikan ke pesantren. Menggunakan pendekatan kualitatif dengan metode studi kasus, penelitian ini menggali proses pelaksanaan, materi ajar, serta hasil evaluasi program dari aspek kesiapan mental (kognitif), spiritual (afektif), dan sosial (psikomotorik). Hasil penelitian menunjukkan bahwa program ini mampu meningkatkan kemampuan baca tulis Al-Qur’an, pemahaman dasar ilmu keislaman (Nahwu, Shorof, Pegon), kedisiplinan ibadah, serta kemandirian dan tanggung jawab sosial peserta didik. Penilaian tengah dan akhir program menunjukkan peningkatan skor pada seluruh indikator, dengan dukungan positif dari orang tua peserta. Program ini juga terbukti membantu siswa beradaptasi lebih baik terhadap kehidupan pesantren. Temuan ini mempertegas pentingnya pendidikan pra-pesantren sebagai jembatan transisi yang efektif dalam sistem pendidikan Islam.